Bridging gendered diversity in a globalizing world: Introduction - Blumen, Orna; Fenster, Tovi; Misgav, Chen (Hagar: Studies in Society and Culture, 2013)
Because gender is often fractured at its intersection with other components of identity, it is critically used to challenge the modern notion of universal participation. [...]the sessions focused on concepts of diversity and multiculturalism, so as to refrain from the reduction of differences to mere demographic categories of analysis. The editors of Hagar, who took part in the gathering in Ein Karem, invited us to serve as guest editors of a special issue of the journal that would highlight some of the themes raised and discussed in the meeting. Since the vast majority of papers presented challenging and interesting research our choice was difficult and we were constrained by available space and deadlines.